2008
DOI: 10.1155/2008/140894
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a New Fine Particle Impact Damper

Abstract: The energy dissipation mechanisms of conventional impact damper (CID) are mainly momentum exchange and friction. During the impact process, a lot of vibration energy cannot be exhausted but reverberated among the vibration partners. Besides, the CID may produce the additional vibration to the system or even amplify the response in the low-frequency vibration. To overcome these shortcomings, this paper proposes a new fine particle impact damper (FPID) which for the first time introduces the fine particle plasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Du et al [38] found that the particles, when clamped by normal impact of two large bodies, can absorb a large amount of kinetic energy. Structures or devices equipped with the FPID could have good performance in vibration environment, which has been verified by experiments [36].…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…Du et al [38] found that the particles, when clamped by normal impact of two large bodies, can absorb a large amount of kinetic energy. Structures or devices equipped with the FPID could have good performance in vibration environment, which has been verified by experiments [36].…”
Section: Introductionmentioning
confidence: 60%
“…Experimental details can be found in [36]. The cantilever beam made of steel is 315 mm in length, 45 mm in width, and 2.1 mm in thickness.…”
Section: Comparison Between Numerical and Experimental Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, some structural vibration control technologies such as particle damper, impact damper, particle tuned mass damper, and viscoelastic damper [7][8][9][10] are used in the aerospace field at present. A reaction wheel isolator assembly [11] made up of a set of six machined spring elements with bonded viscoelastic material was designed to reduce microvibration transmitted to the optical payload of Chandra Observatory.…”
Section: Introductionmentioning
confidence: 99%